Smoking Parameters in Coronary Heart Disease Patients Treated at Dr. Hasan Sadikin General Hospital Bandung, Indonesia - Prabhaswara, Agastya; Ikhsani, Rizkania; Bijaksana, Transiska Liesmadona; Wahjoepramono, Nicolaus Novian Dwiya; Tarsidin, Najmi Fauzan; Tiksnadi, Badai Bhatara (Majalah Kedokteran Bandung, 2024)
The association between smoking and coronary heart disease (CHD) has been studied extensively, though smoking parameters that contribute to the development of CHD may still need to be studied further. This cross-sectional study aimed to describe the characteristics of smoking parameters, including the number of cigarettes smoked, age when started smoking, duration of smoking, and cessation of smoking, in CHD patients treated at Dr. Hasan Sadikin General Hospital, Indonesia. CHD patients aged ≥18 years were included from the cardiology outpatient clinic and hospital wards. Smokers (current smokers/quit smoking <6 months) and ex-smokers (quit smoking ≥6 months) were considered patients who had a history of smoking. The Brinkman index, i.e., duration of smoking x number of cigarettes/day, was used to measure the degree of smoking that were categorized into mild, moderate, and severe smokers. Eighty-seven subjects diagnosed with CHD were recruited in this study. Seventy-seven percent of the subjects were male, and the mean age of subjects studied was 58.5±10.4 years. Among all subjects, a history of smoking was found in 66.7% (37.9% smokers and 28.7% ex-smokers), with all composed of male subjects. The age of subjects who had a history of smoking was 20 (15-35) years. Most were moderate smokers (74.1%) from Brinkman Index measurement. Smoking history has a significant association with male sex, lower total cholesterol, and lower LDL levels (p-value <0.05).